The Development of Teaching Material Based on Multiple Intelligence Theory of Central Learning Model for Childhood Aged 5-6 Years - Ulfa, Siti Maria; Wiryokusumo, Iskandar; Leksono, Ibut Priono (International Journal of Educational Technology and Learning, 2019)
This study aims to develop teaching materials based on the multiple intelligences theory in central learning models for childhood aged 5-6 years, in the form of teacher manuals and student worksheets. This study uses a development model of ADDIE (Analysis, Design, Development, Implementation, Evaluation) which contains needs analysis and curriculum analysis to test the effectiveness of instructional materials. The results of the validation of teaching material books were analysed using descriptive presentations. Field trials of teaching material books were conducted on 22 students as research subjects. The results of the development of teaching material books based on the multiple intelligences theory of content / material experts scored 82%, from learning media experts scored 95% and from peers obtained a score of 94%. The use of teaching material books in learning gets good responses from principals and teachers based on the interview results stating that the use of teaching materials based on the multiple intelligences theory in the central learning model makes students become creative and active so learning becomes fun. Whereas from the observation results, the scale of students 'developmental achievements shows students' development in accordance with the expectations and activeness of the students very well. The results of the research obtained can be concluded that the development of teaching materials in the form of teacher manuals and student worksheets based on the multiple intelligences theory in the centre of learning model aged 5-6 years is valid and suitable for use in classroom learning.